Hijrah Rasul Dari Sudut Siyasah Aturguna Modal Insan - Wan Mohd Yusof, Wan Chik; Hasanulddin, Mohd; Basri, Ibrahim; Rohaizan, Baru (2009)
Rasulullah s.a.w. is the axis that reflects the ultimate model of human perfection, be it from personal experiences, family, community, nationally and even internationally. Therefore, he is well equipped with a diversity of advantages such as the continuous flow of the holy revelation, the protection of al-ismah and vast experiences. To ensure that each aspect of his life is inherited, understood and practiced by the ummah, Islamic scholars dating from the generation of the Companions, the Tabie'n and later generations have been working very hard in compiling and documenting the seerah or the life journey of the Prophet. Among the most interesting parts - but hardly mentioned -is the aspect of his brilliant planning in organizing and optimizing the usage of available human resources to pull out this dramatic and thrilling moment. As such, this article will give a brief outline on this momentous event. Next it will discuss the characters involved in completing the mission and their significance as the brain of human resource management. It is believed that this brief outline might provide the country with the much needed Hijra foundation in planning, developing, and utilizing human resources effectively in this ever challenging era.